The Impact of Turats Based Arabic Learning in Islamic Boarding Schools on Madrasah Aliyah’s Students’s Learning Outcomes/Atsru Ta’lim al-Lughah al-Arabiyah al-Qaim ala Kitab al-Turats fi al-Mahad ala Nataij Ta’allum Thullab al-Madrasah al-Aliyah - Rifka Arifatul Choridah; Nawawi Aulia Muhammad; Zahrohtur Robiyah; Qomi Akit Jauhari (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2026)
This research investigates how studying the Jurumiyah book (turats) influences students' comprehension of Arabic grammar and their educational results at MAN 3 Jombang. The investigation is founded on the belief that learning Arabic via traditional Islamic literature in Islamic boarding schools can enhance students' performance in formal educational settings. A mixed-methods strategy was utilized for this study, integrating both qualitative and quantitative data. Information was gathered through classroom observations, interviews, surveys, and examination of students' academic records. The quantitative data were analyzed by applying descriptive statistics and simple linear regression to explore the connection between the use of the Jurumiyah book and student performance, while qualitative data aided in interpreting the results. The findings reveal that employing the Jurumiyah book positively influences students’ academic achievements. Learners who engage with Arabic through this traditional text show a stronger grasp of Arabic grammar and typically attain high levels of academic success. These outcomes imply that incorporating turats-centered learning in Islamic boarding schools can enhance students' achievements in formal madrasah education. This research adds to the dialogue surrounding Arabic language instruction by emphasizing the importance of classical Islamic texts as a valuable supplementary educational tool for enhancing students' grammatical skills and academic success.تبحث هذه الدراسة في تأثير دراسة كتاب الجروميات على فهم الطلاب لقواعد اللغة العربية ونتائجهم الدراسية في المدرسة العالية الإسلامية 3 جومبانج. وتستند الدراسة إلى الاعتقاد بأن تعلم اللغة العربية من خلال الأدب الإسلامي التقليدي في المعهد يُحسّن أداء الطلاب في البيئات التعليمية الرسمية. وقد استُخدم في هذه الدراسة منهج بحثي مختلط، يجمع بين البيانات النوعية والكمية. جُمعت المعلومات من خلال الملاحظات الصفية، والمقابلات، والاستبيانات، وفحص السجلات الأكاديمية للطلاب. حُللت البيانات الكمية باستخدام الإحصاء الوصفي والانحدار الخطي البسيط لاستكشاف العلاقة بين استخدام كتاب الجروميات وأداء الطلاب، بينما ساعدت البيانات النوعية في تفسير النتائج. وتُظهر النتائج أن استخدام كتاب الجروميات يُؤثر إيجابًا على التحصيل الدراسي للطلاب. فالمتعلمون الذين يتفاعلون مع اللغة العربية من خلال هذا النص التقليدي يُظهرون فهمًا أعمق لقواعد اللغة العربية، ويحققون عادةً مستويات عالية من النجاح الأكاديمي. تشير هذه النتائج إلى أن دمج المناهج الدراسية القائمة على التوراة في المعهد يُمكن أن يُحسّن تحصيل الطلاب في التعليم النظامي بالمدارس الدينية. يُضيف هذا البحث إلى الحوار الدائر حول تدريس اللغة العربية من خلال التأكيد على أهمية النصوص الإسلامية الكلاسيكية كأداة تعليمية تكميلية قيّمة لتعزيز مهارات الطلاب النحوية ونجاحهم الأكاديمي.